Establishing a Database of Competition between ISPs Based on Python Language - He, Hanyue (Journal of physics. Conference series, 2020)
Nowadays, we have entered the era of 5G. And the application of the Internet surrounds our daily life. People need to rely on broadband products provided by different Internet service providers (ISP) when they access the Internet. People often compare the speed and the cost of Internet access between different providers. However, monopolistic behavior in the industry is severe in some countries, which may result in users having to withstand higher network access prices and lower quality broadband products. Therefore, the competition between ISPs is a direct influencing factor for users to use the network. This article first highlights the importance of competition among ISPs. And secondly, choose the European authoritative website, crawl the data, and manipulate it at the first step. Finally, this paper summarizes the ISPs competition data sets that can be used for subsequent model analysis. The author will elaborate on the relationship between competition and flow price in subsequent paper.